Sincerity and Transmission. (29th August 2014) - Wright, Stephen
Abstract: According to some theories of testimonial knowledge, testimony can allow you, as a knowing speaker, to transmit your knowledge to me. A question in the epistemology of testimony concerns whether or not the acquisition of testimonial knowledge depends on the speaker's testimony being sincere. In this paper, I outline two notions of sincerity and argue that, construed in a certain way, transmission theorists should endorse the claim that the acquisition of testimonial knowledge requires sincerity.